Kinetic Study of Lithium Leaching from Sidoarjo Mud Using Sulfuric Acid - Maulidia, Anisa; Sujoto, Vincent Sutresno Hadi; Sudarmaja, Dewa Putu Agus; Putri, Januarti Jaya Eka; Jenie, Siti Nurul Aisyiyah; Astuti, Widi; Supriyatna, Yayat Iman; Warmada, I. Wayan; Sutijan, Sutijan; Anggara, Ferian; Petrus, Himawan Tri Bayu Murti (Springer Science and Business Media Deutschland GmbH, 2023)
With the rapid development of renewable energy technology, such as electricity reserves, to store energy for electric or electric vehicles, environmentally friendly energy sources are expected to continue to be fulfilled according to mobility and stationary energy needs. Lithium is the most attractive candidate for energy storage development. The presence of lithium in Indonesia in the Sidoarjo mud content is interesting to be used as an alternative source of raw materials. During the research, sulfuric acid acted as a solvent, and hydrogen peroxide acted as an oxidation agent. Lithium recovery will be studied using a leaching process at various temperatures (30, 45, and 60 Â°C) and sulfuric acid concentrations (0.5, 1, 2, 3, 4, and 6 mol/L). The increasing temperature, sulfuric acid concentration, and hydrogen peroxide concentration will directly affect the lithium recovery. An increase in sulfuric acid concentration will be directly proportional to the recovery of lithium in the solution. Optimum conditions were obtained at varying 6 mol/L sulfuric acid concentrations and 60 Â°C temperature variations. The shrinking core model (SCM) studied leaching kinetics, and ash layer diffusion acted as a rate-controlling process. The activation energy of the leaching process was obtained at 38.90 kJ/mol. Graphical Abstract: Figure not available: see fulltext..